Harmonisasi Hukum Di Indonesia Dalam Perspektif Teori Hukum Pembangunan - Kriswanto, Kriswanto (Faculty of Sharia, Institut Agama Islam Negeri (IAIN) Metro, Lampung, Indonesia., 2022)
Law is one of the instruments needed to facilitate various social developments. Law is an important thing in the process of community development, especially for countries that identify law as a written rule. This paper is a normative juridical research, with data sources on primary legal materials and secondary legal materials. The results show that the harmonization of law in Indonesia is marked by a simplification in the formation of laws through the omnibus law/omnibus bill method, with the existence of this omnibus law, several regulations can be simplified into one law. So that the regulations can be simpler and can answer many aspects of the legal needs of the community. So the researcher assumes that the harmonization of laws carried out by the government, in order to simplify regulations and meet the needs of the community, is very much in accordance with the Legal Development Theory which is still relevant to be used as a guide and guide for Harmonization of Law in Indonesia. .